2018
DOI: 10.1016/j.jclepro.2018.01.110
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable supply chain quality management: A systematic review

Abstract: Maintaining profitability measures while conducting business through environmentally and socially sustainable operations is an optimization challenge for organizations globally and for our society. Aiming to contribute to the research streams on this global challenge, this paper studies the state of the art literature on two management methodologies along with sustainability management from an integration perspective: quality management with its intraorganizational focus and supply chain management with its in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
129
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 217 publications
(155 citation statements)
references
References 79 publications
1
129
0
3
Order By: Relevance
“…Further, the commitment and support of senior leadership are critical factors for SSCM implementation (Bastas & Liyanage, ; Green, Zelbst, Meacham, & Bhadauria, ; Wolf, ). Lieb and Lieb () and Sharfman, Shaft, and Anex () demonstrated that ethical motives and sustainability values are important sources of motivation that influence the senior leadership to go beyond legal compliance and profit motives and demonstrate their “desire to do the right thing.” In spite of this, some studies reported that insufficient management support may reduce SSCM implementation (Correia, Howard, Hawkins, Pye, & Lamming, ).…”
Section: Drivers For and Barriers To Sscm Implementationmentioning
confidence: 99%
“…Further, the commitment and support of senior leadership are critical factors for SSCM implementation (Bastas & Liyanage, ; Green, Zelbst, Meacham, & Bhadauria, ; Wolf, ). Lieb and Lieb () and Sharfman, Shaft, and Anex () demonstrated that ethical motives and sustainability values are important sources of motivation that influence the senior leadership to go beyond legal compliance and profit motives and demonstrate their “desire to do the right thing.” In spite of this, some studies reported that insufficient management support may reduce SSCM implementation (Correia, Howard, Hawkins, Pye, & Lamming, ).…”
Section: Drivers For and Barriers To Sscm Implementationmentioning
confidence: 99%
“…The test for mediation in this study follows Baron and Kenny (1986) four steps to test for mediation. Per Baron and Kenny (1986) if M mediates an X-Y causal relationship then:…”
Section: The Role Of Collaboration In the Relationship Between Sustaimentioning
confidence: 99%
“…Per Baron and Kenny (1986) procedure, the effect of the independent variable on the dependent variable must be reduced with the presence of the mediator. Thus patch c, which is already found in step 1, must be lesser than c"…”
Section:  Test 2: Impact Of External Pressures (Sustainability Drivementioning
confidence: 99%
“…Adicionalmente, de acuerdo con Katunzi (2011), la mayoría de las barreras de la SCI corresponden a factores blandos, entre estos el capital social (CS), que se ha asociado positivamente con las relaciones de la SCM (Roden y Lawson, 2014;Son et al, 2016), pero que no ha sido suficientemente estudiado como determinante en la SCI (Bastas et al, 2018;Borgatti y Li, 2009). En este sentido, se han identificado variables que pueden mediar en el proceso de la SCI.…”
Section: Introductionunclassified